Validation of otolith daily increments in early juveniles of shanny Lipophrys pholis - Carvalho, M. G.
To assess the periodicity of micro-increment formation in otoliths of Lipophrys pholis, 90 early juveniles were immersed in alizarin red S or tetracycline hydrochloride for 24 h and sacrificed after 10, 20 and 30 days. The number of micro-increments viewed under light microscopy was significantly related to the duration of the experimental period, and the slopes of the linear regressions were not significantly different from 1. This study indicates that micro-increments in sagittae were deposited daily and can be used as reliable sources of age information for L. pholis.